A comparative analysis of the requirements for the use of data in biobanks based in Finland, Germany, the Netherlands, Norway and the United Kingdom. (December 2014) - Moraia, Linda Briceño; Kaye, Jane; Tasse, Anne Marie; Knoppers, Bartha M.; Mitchell, Colin; Soini, Sirpa; Hoppe, Nils; Wallace, Susan E.; Øien, Morten
To understand the causes of disease and improve diagnosis and treatment regimes, biomedical researchers need access to large numbers of well-characterized data and samples. Over the past decade, biobanks have been established across Europe to collect and manage access to data and samples. The challenge that we face is how to develop the tools and collaborations to enable researchers to access samples and data from a network of biobanks, rather than applying to individual biobanks. One of the perceived stumbling blocks to achieving this is represented by the different legal requirements in each country. The aim of the BioSHaRE-European Union (EU) project is to address these challenges by developing tools and methods for researchers to access and use pooled data from different cohort and biobank studies. The purpose of this article is to identify and compare the key legal requirements regarding research use of data across biobanks based in Finland, Germany, the Netherlands, Norway and the UK. Our investigation starts with the analysis of the key differences for the use of data between these countries. As a result, we identified three key areas where legal requirements differ across the five BioSHaRE-EU jurisdictions, namely, in the definition of personal data, the requirements regarding pseudonymization and processing for medical research purposes. This article provides an overview of these differences and describes them in the light of the proposed EU regulation on data protection.